The Cultural Legacy of Emhan Ring Ladies Series I, II and III - Hishamuddin, Siri (UNIMAS Publisher, 2025)
This series reimagines the cultural legacy of the Sembhan ring lady through digital photography, VR and AI. Each image blends ancestral memory with contemporary technology, creating an immersive experience where history becomes interactive. The work invites viewers to encounter heritage anew by merging realism, storytelling and digital augmentation into a living visual dialogue.